2015
DOI: 10.1002/pssr.201510243
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of hard magnetic (Fe,Cr)3Sn2 intermetallic compound

Abstract: By high‐throughput screening Fe–Sn–Cr, (Fe,Cr)3Sn2 (Fe53.5Cr6.5Sn40) with high potential as new hard magnetic compound is discovered. To produce the compound in large amounts a special procedure is needed. By quantitative microscopy and magnetometry promising intrinsic properties, Js ∼ 0.9 T, K1 ∼ 1.7 MJ/m3, TC ∼ 612 K, are found with K1 increasing with temperature. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several phase diagrams of material systems have been constructed using different combinatorial approaches [23,24], e.g. thin film deposition [25] and bulk high-throughput techniques, such as reactive diffusion method [26], and reactive crucible melting [7,[27][28][29][30][31].…”
Section: B Experimentsmentioning
confidence: 99%
“…Several phase diagrams of material systems have been constructed using different combinatorial approaches [23,24], e.g. thin film deposition [25] and bulk high-throughput techniques, such as reactive diffusion method [26], and reactive crucible melting [7,[27][28][29][30][31].…”
Section: B Experimentsmentioning
confidence: 99%
“…4 Possible candidate materials for a rare-earth-free permanent magnet are FeSn based alloys. 5 Whereas Fe 3 Sn shows an easy-plane anisotropy, ab initio simulations show that substituting Sn by Sb may lead to uniaxial anisotropy. 6 Skomski et al 7 showed another way to create a uniaxial magnet from easy-plane materials.…”
mentioning
confidence: 99%